Alternatives in the design of sovereign green bonds - Daniel C. L. Hardy (The Vienna Institute for International Economic Studies (wiiw), 2022)
Many governments have started issuing 'green' bonds tied to expenditures on projects with environmental objectives such as climate change mitigation. While well-intentioned, issuance of a green bond by an investment-grade sovereign has no environmental impact, leaves funding costs unchanged, offers no protection from environmental risks, does little for the healthy development of the market for green financing, and represents poor public sector governance. A performance-linked bond whose payoff depends on overall greenhouse gas emissions would be more transparent, cheaper to administer, and more conducive to long-term policy commitment, but may be politically more demanding and difficult for markets to price.
Keywords: G18; H63; Q58; 330; green bond; sustainable finance; sovereign debt; fiscal transparency